2017
DOI: 10.3389/fpls.2017.01586
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Septoria tritici Blotch Resistance in Ethiopian Durum Wheat Landraces

Abstract: Septoria tritici blotch (STB) is a devastating fungal disease affecting durum and bread wheat cultivation worldwide. The identification, development, and employment of resistant wheat genetic material is the key to overcoming costs and limitations of fungicide treatments. The search for resistance sources in untapped genetic material may speed up the deployment of STB genetic resistance in the field. Ethiopian durum wheat landraces represent a valuable source of such diversity. In this study, 318 Ethiopian dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 59 publications
(72 reference statements)
9
48
0
Order By: Relevance
“…Although the markers used in the current study were previously reported to be tightly linked to the blast resistance genes (Srivastava et al, 2017), the association analysis demonstrated the possible effect of these markers on the agro-morphological traits. These results were in accordance with those reported by a genome-wide association study conducted in wheat (Kidane et al, 2017). In their study, the authors pointed out that the presence of putative quantitative trait loci (QTL) is associated with blotch resistance, which were also found to be overlapped with the QTL associated with different agronomic traits.…”
Section: Genetic Association Between Molecular Markers and The Agro-msupporting
confidence: 90%
See 1 more Smart Citation
“…Although the markers used in the current study were previously reported to be tightly linked to the blast resistance genes (Srivastava et al, 2017), the association analysis demonstrated the possible effect of these markers on the agro-morphological traits. These results were in accordance with those reported by a genome-wide association study conducted in wheat (Kidane et al, 2017). In their study, the authors pointed out that the presence of putative quantitative trait loci (QTL) is associated with blotch resistance, which were also found to be overlapped with the QTL associated with different agronomic traits.…”
Section: Genetic Association Between Molecular Markers and The Agro-msupporting
confidence: 90%
“…In this context, DNA markers serve as significant tools to identify the resistance genes in rice breeding programs without the need for conventional inoculation methods (Hayashi et al, 2010). Although the resistance genes mainly confer resistance to a pathogen, in some instances, they also cosegregate with other marker genes associated with quantitative traits (Kidane et al, 2017;Zhang et al, 2017). Therefore, it is of high interest to understand other putative roles, if there are any, of DNA markers associated with disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Thousands of FVs evolved in Ethiopia with the simultaneous contribution of natural and artificial selection, following a complex pattern of trait selection and amplification (Kidane et al, 2017b;Mancini et al, 2017). Therefore, the Ethiopian durum wheat is a source of several adaptive traits of breeding relevance, including disease resistance alleles to rusts and Septoria (Kidane et al, 2017a;Liu et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…GWAS has been widely adopted in different plant species to overcome some of the constraints inherent to bi-parental linkage mapping, such as the limited genetic diversity explored (Barabaschi et al 2016). GWAS has been successfully used in both durum and common wheat, mainly focused to resistance to pathogens (e.g., Kidane et al 2017), grain yield, heading date, plant height, number of fertile tillers, biomass, and number of seeds per spike (Zanke et al 2014a(Zanke et al , b, 2015Mengistu et al 2016).…”
Section: Introductionmentioning
confidence: 99%